The OASIS3-MCT Coupling Interface for ICON-CLM - Ho-Hagemann, Ha Thi Minh (Zenodo, 2022)
Synopsis ICON_OMCI is the new external coupling interface for the ICON-CLM model (Pham et al., 2021) using the OASIS3-MCT coupler (Valcke et al., 2015) to couple ICON-CLM with the ocean model NEMO (Madec et al., 2017) and the hydrological discharge model HD (Hagemann et al., 2020; Hagemann and Ho-Hagemann, 2021) in the GCOAST-AHOI coupled system model (Ho-Hagemann et al., 2020), a sub-set of the G eesthacht C oupled c OA stal model S ys T em GCOAST . ICON-CLM is the regional climate model that has been developed by the Deutscher Wetterdienst (DWD) and the Climate Limited-area Modeling Community (CLM-Community) since 2017. ICON-CLM is the Climate Mode of ICON-LAM (ICON-Limited Area Mode, based on the numerical weather prediction model ICON-NWP) of the ICON (Icosahedral Nonhydrostatic) model (Zängl et al., 2015). ICON has been developed since 2001 as the result of a cooperation between DWD and Max Planck Institute for Meteorology (MPI-M) (see an overview of ICON). It currently comprises two versions (ICON-NWP, ICON-ESM) that share the same dynamics but have different physical packages. ICON-ESM comprises atmospheric, land, river routing, ocean-sea ice and biogeochemical compartments, while the Aerosols and Reactive Trace gases (ART) model was implemented into ICON-NWP. ICON can be set up to operate on different high performance computing systems such as at the German Climate Computing Center (DKRZ, Hamburg, Germany), at DWD (Offenbach, Germany) or at FZJ (Forschung Zentrum Jülich, Germany). ICON-CLM currently contains a set of technical adaptations for climate applications. Motivation Including major compartments of the climate system, ICON-ESM has YAC (Yet Another Coupler; Hanke et al., 2016) to couple the component models together. Unfortunately, up to date, the YAC coupling is available only for ICON-A (i.e. the global atmospheric ICON model with MPI-M ECHAM physics) to couple with ICON-O ...